Pickering emulsions and their use in production of polymer nanostructured materials - B. V. Pokidko; D. A. Botin; M. Yu. Pletnev (Тонкие химические технологии)
In this article both types of Pickering emulsions – oil/water and water/oil – and their applications in the synthesis of different polymers have been considered. Pickering emulsions are dispersions stabilized by solid particles adsorbed at oil-water interface instead of conventional emulsifier. The influence of various solid particles, their amount and interaction on emulsions formation, stability and morphology with various suspended solid particles have been considered. Phase inversion phenomena and factors (such as wettability of solid particles) affecting them have been described. The interest to Pickering emulsions for the last decade is highly fueled by eco-friendly and cost-effective manufacture of hybrid polymer particles and nanocomposites with supracolloidal structures. The Pickering emulsion polymerization or suspension polymerization allows preparing in situ reinforced nanostructural polymer composites, unusual latexes and microcapsules with unique properties.